Zirconium-based laminated hydromagnesite composite powder as well as preparation method and application thereof

Through the preparation of zirconium substrate layered water magnesite composite powder, the color change of natural water magnesite powder and the environmental protection of traditional functional materials are solved, and the efficient and low-cost functional improvement is achieved. It is suitable for composite materials and improved Mechanics and flame retardant properties.

CN119177033APending Publication Date: 2024-12-24JIANGXI GUANGYUAN CHEM +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411292689.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-14
Publication Date
2024-12-24

AI Technical Summary

Technical Problem

Natural water magnesite powder is prone to discoloration during the surface functionalization process, and traditional functional materials are costly and have a great environmental impact, and lacks efficient means of green and environmental protection to perform secondary functionalization.

Method used

The preparation method of zirconium substrate layered water magnesite composite powder is adopted. By heat treatment of zirconium phosphate powder and combined with sugar and silane coupling agent, a multi-layer structure is formed through spray technology to modify the water magnesite composite powder. to improve its hardness and functionality.

Benefits of technology

The multi-layer modification of natural water magnesite has been realized, which improves its hardness, flame retardancy and smoke suppression, reduces oil absorption value, and forms multi-level structural composite powder, which is suitable for low-carbon and environmentally friendly development, is suitable for composite materials, and is improved. Mechanical properties and flame retardant properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119177033A_ABST
    Figure CN119177033A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of functional materials, and provides zirconium-based laminated hydromagnesite composite powder as well as a preparation method and application thereof. The method comprises the following steps: carrying out heat treatment on zirconium phosphate powder, and dispersing in a first solvent to obtain a zirconium-based mixed solution; sugar, a silane coupling agent and a second solvent are mixed, and a sugar-containing mixed solution is obtained; spraying the sugar-containing mixed solution into hydromagnesite powder, and continuously mixing to obtain modified hydromagnesite composite powder; the zirconium-based mixed solution and the silane coupling agent solution are sequentially sprayed into the modified hydromagnesite composite powder, a continuous reaction is conducted after spraying is completed, and the zirconium-based laminated hydromagnesite composite powder is obtained. The composite powder contains a plurality of components and a multi-stage structure, has the characteristics of being green, environmentally friendly, sustainable, wide in source and the like, is low in price, realizes organic multi-layer modification of natural hydromagnesite by combining the components in a structure reconstruction mode, and also endows the composite powder with a plurality of functions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of functional materials, and in particular to a zirconium-based layered hydromagnesite composite powder and a preparation method and application thereof. Background Art

[0002] Natural stone ore is a precious stone resource in nature. Its added value and application range can be effectively improved through surface functionalization. It can be seen that surface functionalization is a must. Natural hydromagnesite is a kind of natural stone ore powder whose main component is basic magnesium carbonate. It is mostly stacked in layers (sometimes in fibrous form) and is the natural mineral with the highest magnesium content discovered so far. In its natural state, although it already has the advantages of good filling, flame retardancy, smoke suppression, non-toxicity, non-volatility, and easy storage, it still needs surface functionalization to further improve its comprehensive performance. In the process of surface functionalization, due to the insufficient hardness of this type of natural powder, it is difficult to maintain its original morphology, and even the color will change significantly, such as yellowing and blackening, grayish white and roughness. Based on this, how to effectively avoid the discoloration of low-hardness natural stone ore powder during processing needs to be solved urgently.

[0003] The simple reconstruction of natural products can effectively avoid the large-scale consumption of organic reagents and raw material intermediates, and can better adapt to the urgent needs of environmental protection development. In the actual industrial production process, the preparation of traditional artificially synthesized functional materials is not only costly, but also time-consuming and labor-intensive, and difficult to degrade after failure. In contrast, natural products do not have such concerns. They are relatively green and environmentally friendly. Even after failure, they can still exist in nature in a very inert manner and will not cause secondary damage to the environment. Therefore, it is urgent to combine a variety of natural products in a simple, fast, and green way, especially to develop green, environmentally friendly, efficient and convenient means to perform secondary functionalization on them, which can not only further enhance the added value and functionality of natural hydromagnesite minerals, but also conform to the current development concept of low-carbon and environmental protection.

[0004] Among many natural products, natural sugars are a very abundant class of natural bio-organic molecules and are the main source of metabolic energy for plants and animals that feed on plants. m (H 2 O) nTherefore, they are often called carbohydrates, and the main types are: monosaccharides, disaccharides, oligosaccharides and polysaccharides. Sugars are also excellent candidates for complexing a variety of functional materials. More importantly, the CO and CC bonds between these three structural units, and the hydrogen bonds between polycyclic heterocycles and hydroxyl groups can promote the formation of a complex three-dimensional network structure of natural sugars. Not only that, multiple internally rotating chemical bonds can also deform when subjected to external forces, effectively buffering the external impact force. It can be seen that this type of natural product can not only serve as an adhesive for multiple components, but also effectively achieve a buffering effect. The various aromatic ring structures contained in its structure can even quickly carbonize at high temperatures to form an effective physical barrier layer.

[0005] At present, this type of natural product is rarely used in the organic buffer layer of natural inorganic mineral powders, and is also rarely used in the reconstruction and bonding of multiple inorganic mineral powders. Summary of the invention

[0006] The purpose of the present invention is to provide a zirconium-based layered hydromagnesite composite powder and a preparation method and application thereof in order to overcome the deficiencies of the prior art.

[0007] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0008] The present invention provides a method for preparing a zirconium-based layered hydromagnesite composite powder, comprising the following steps:

[0009] 1) heat-treating zirconium phosphate powder to obtain zirconium substrate layer powder, and dispersing the zirconium substrate layer powder in a first solvent to obtain a zirconium-based mixed solution;

[0010] mixing sugar, silane coupling agent and second solvent to obtain sugar-containing mixed solution;

[0011] 2) spraying the sugar-containing mixed solution into the hydromagnesite powder, and continuously mixing after the spraying is completed to obtain a modified hydromagnesite composite powder;

[0012] 3) Spraying the zirconium-based mixed solution and the silane coupling agent solution into the modified hydromagnesite composite powder in sequence, and continuing the reaction after the spraying is completed to obtain the zirconium-based layered hydromagnesite composite powder.

[0013] Preferably, the median particle size of the zirconium phosphate powder in step 1) is 1.0-3.0 μm, the heat treatment is carried out in a nitrogen atmosphere, the heat treatment temperature is 200-500° C., and the heat treatment time is 1-60 min; the dispersion rate is 1200-5000 r / min, and the dispersion time is 10-120 min.

[0014] Preferably, in step 1), the first solvent is an alcohol-water solution, in which the volume ratio of alcohol to water is 1:1 to 30; the alcohol includes ethanol, methanol, ethylene glycol, neopentyl alcohol, isopropanol or propanol; and the second solvent is an ethanol-water solution, in which the volume ratio of ethanol to water is 1 to 10:1.

[0015] Preferably, in step 1), the concentration of the zirconium-based mixed solution is 1 to 10 mol / L; the molar ratio of the sugar to the silane coupling agent is 1:0.1 to 2.0, and the concentration of the sugar-containing mixed solution is 1 to 5 mol / L;

[0016] The sugar comprises one or more of D-galactose, glucose, sialic acid, D-trehalose, sodium hyaluronate, sorbitol, glucosamine, D-mannose, sucrose, arabinose, N-acetyl-D-glucosamine, fructose, lactose, maltose, melibiose, xylose, lactulose, raffinose, erythritol, L-rhamnose, stachyose, D-tagatose, voglibose, lactobionic acid, D-allose, nesitose, alginic acid, maltitol, mannotriose, D-arabitol, sweet alcohol, D-lyxose and α-lactose;

[0017] The silane coupling agent and the silane coupling agent in step 3) include one or more of bis-(3-(triethoxysilane)propyl)-disulfide, bis-(3-(triethoxysilane)propyl)-tetrasulfide, bis(3-triethoxysilylpropyl)amine, bis(3-trimethoxysilylpropyl)amine, 1,3,5-tris(trimethoxysilylpropyl)isocyanurate, 1,2-bis(triethoxysilyl)ethane and 1,2-bis(trimethoxysilyl)ethane.

[0018] Preferably, in step 2), the hydromagnesite powder is first stirred before spraying, and second stirred during spraying, the first stirring rate is 100-1000 r / min, the temperature is 25-50° C., and the time is 10-40 min;

[0019] The spraying rate is 1-40 mL / min, the temperature is 40-80° C., and the continuous mixing time is 10-60 min; the stirring rates in the second stirring and the continuous mixing are independently 100-1000 r / min.

[0020] Preferably, in step 2), the molar mass ratio of sugars to hydromagnesite powder in the sugar-containing mixed solution is 1-5 mol:10 kg; and the median particle size of the hydromagnesite powder is 1.0-4.5 μm.

[0021] Preferably, in step 3), the mass ratio of the zirconium-based mixed solution to the modified hydromagnesite composite powder is 1:0.05-0.8; the mass molar ratio of the zirconium-based mixed solution to the silane coupling agent is 1kg:0.1-2mol;

[0022] The concentration of the silane coupling agent solution is 1-10 mol / L, the solvent of the silane coupling agent solution is ethanol aqueous solution, and the volume ratio of ethanol to water is 1:1-5.

[0023] Preferably, in step 3), the modified hydromagnesite composite powder is first stirred before spraying, and the first stirring rate is 300 to 900 r / min and the time is 10 to 60 min;

[0024] The spraying rate of the zirconium-based mixed solution is 1 to 50 mL / min, the spraying rate of the silane coupling agent solution is 1 to 20 mL / min, and the temperature of the silane coupling agent solution is increased during the spraying process, the temperature increase rate is 5 to 20° C. / min, and the target temperature is 90 to 120° C.;

[0025] The continuous reaction time is 10 to 30 minutes, and the stirring rate during the continuous reaction is 500 to 1200 r / min.

[0026] The invention also provides a zirconium-based layered hydromagnesite composite powder prepared by the preparation method. The median particle size of the zirconium-based layered hydromagnesite composite powder is 1.0-5.0 μm.

[0027] The invention also provides application of the zirconium-based layered hydromagnesite composite powder in a polyvinyl alcohol / gelatin composite material.

[0028] The beneficial effects of the present invention include the following:

[0029] (1) The zirconium substrate layered hydromagnesite composite powder (ZrO 2 -LFS-NMP) contains multiple components and multi-level structures, especially a large amount of natural products, which are green, environmentally friendly, sustainable, widely available and inexpensive. They are combined together through structural reconstruction to achieve organic multi-layer modification of natural hydromagnesite, and also give the composite powder multiple functionalities, which is in line with the current concept of low-carbon, environmentally friendly and sustainable development.

[0030] (2) The zirconium-based layered hydromagnesite composite powder of the present invention makes full use of the characteristics of the collapse and compression of the zirconium phosphate layered structure to form zirconium oxide, so that it can provide a high-hardness surface layer on the outside, providing an effective shell barrier for its whiteness. At the same time, the adhesive layer composed of natural sugar and silane in the middle can effectively improve the distribution state and physical stability of the surface zirconium-based layer on the surface of the natural hydromagnesite powder. The natural hydromagnesite powder inside itself has good flame retardancy and smoke suppression, and has a good filling effect. The three-layer multiple structure and the mutual combination of multiple components can form a physical structure of hard shell-elastic layer-soft core. The surface zirconium phosphate / zirconium oxide layer has good solid The acid catalytic property can significantly promote carbonization. During the self-combustion process, it can adhere to the internal ceramic precursor MgO skeleton to form a reinforced carbon layer with high thermal stability and physical barrier properties. The elastic layer in the middle can effectively help increase the amount of carbonization. After being combined with silane, the surface hard shell and the soft core can be connected by chemical grafting. The internal natural hydromagnesite effectively releases a large amount of non-combustible gas during the pyrolysis process, and forms a MgO product with high heat resistance and stability, which has a strong synergistic flame retardant and smoke suppression effect. The combination of multiple components can effectively prevent the transfer of heat flow, air flow and mass flow, and comprehensively improve the versatility and multi-functionality of the composite powder.

[0031] (3) The zirconium phosphate / zirconium oxide shell in the zirconium-based layered hydromagnesite composite powder of the present invention can significantly reduce the surface polarity, so that its oil absorption value is significantly reduced, which is conducive to reducing the subsequent processing cost, and helps to improve the dispersibility of the composite powder in the PVA composite material, and also has a good enhancement effect on its mechanical properties. The preparation process of the multi-level structure and multi-component composite powder of the present invention is simple and easy, the process is green and environmentally friendly, and the energy consumption is low. The preparation process uses a large amount of green and environmentally friendly natural products, the overall cost is controllable, and the cost performance is high. It is suitable for large-scale industrial production and has great application potential. The obtained composite powder is white, and the whiteness is well controlled, which effectively avoids the gray-blackening caused by natural hydromagnesite during physical processing. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 It is a schematic structural diagram of the zirconium substrate layered hydromagnesite composite powder of the present invention;

[0033] Figure 2 This is a particle size distribution diagram of the zirconium substrate layered hydromagnesite composite powder prepared in Example 1;

[0034] Figure 3 This is the SEM image of the zirconium substrate layered hydromagnesite composite powder prepared in Example 1. DETAILED DESCRIPTION

[0035] The present invention provides a method for preparing a zirconium-based layered hydromagnesite composite powder, comprising the following steps:

[0036] 1) heat-treating zirconium phosphate powder to obtain zirconium substrate layer powder, and dispersing the zirconium substrate layer powder in a first solvent to obtain a zirconium-based mixed solution;

[0037] mixing sugar, silane coupling agent and second solvent to obtain sugar-containing mixed solution;

[0038] 2) spraying the sugar-containing mixed solution into the hydromagnesite powder, and continuously mixing after the spraying is completed to obtain a modified hydromagnesite composite powder;

[0039] 3) Spraying the zirconium-based mixed solution and the silane coupling agent solution into the modified hydromagnesite composite powder in sequence, and continuing the reaction after the spraying is completed to obtain the zirconium-based layered hydromagnesite composite powder.

[0040] In the present invention, the median particle size (D 50 ) is preferably 1.0-3.0 μm, more preferably 1.2-2.5 μm, more preferably 1.5-2.0 μm; the heat treatment is preferably carried out under a nitrogen atmosphere, and the heat treatment temperature is preferably 200-500°C, more preferably 250-450°C, more preferably 350-400°C; the heat treatment time is preferably 1-60 min, more preferably 10-50 min, more preferably 20-30 min; the dispersion rate is preferably 1200-5000 r / min, more preferably 2000-4000 r / min, more preferably 3000-3500 r / min; the dispersion time is preferably 10-120 min, more preferably 20-100 min, more preferably 40-60 min.

[0041] In the present invention, in step 1), the first solvent is preferably an alcohol aqueous solution, in which the volume ratio of alcohol to water is preferably 1:1-30, more preferably 1:5-25, and more preferably 1:10-20; the alcohol preferably comprises ethanol, methanol, ethylene glycol, neopentyl alcohol, isopropanol or propanol; the second solvent is preferably an ethanol aqueous solution, in which the volume ratio of ethanol to water is preferably 1-10:1, more preferably 3-8:1, and more preferably 5-6:1.

[0042] In the present invention, the concentration of the zirconium-based mixed solution in step 1) is preferably 1-10 mol / L, more preferably 3-8 mol / L, and more preferably 5-6 mol / L; the molar ratio of the sugar to the silane coupling agent is preferably 1:0.1-2.0, more preferably 1:0.5-1.5, and more preferably 1:0.8-1.0; the concentration of the sugar-containing mixed solution is preferably 1-5 mol / L, more preferably 2-4 mol / L, and more preferably 3 mol / L.

[0043] In the present invention, the sugar is a natural sugar, preferably comprising one or more of D-galactose, glucose, sialic acid, D-trehalose, sodium hyaluronate, sorbitol, glucosamine, D-mannose, sucrose, arabinose, N-acetyl-D-glucosamine, fructose, lactose, maltose, melibiose, xylose, lactulose, raffinose, erythritol, L-rhamnose, stachyose, D-tagatose, voglibose, lactobionic acid, D-allose, nesitose, alginic acid, maltitol, mannotriose, D-arabitol, sweet alcohol, D-lyxose and α-lactose;

[0044] The silane coupling agent and the silane coupling agent in step 3) preferably include one or more of bis-(3-(triethoxysilyl)propyl)-disulfide, bis-(3-(triethoxysilyl)propyl)-tetrasulfide, bis(3-triethoxysilylpropyl)amine, bis(3-trimethoxysilylpropyl)amine, 1,3,5-tris(trimethoxysilylpropyl)isocyanurate, 1,2-bis(triethoxysilyl)ethane and 1,2-bis(trimethoxysilyl)ethane.

[0045] In the present invention, the hydromagnesite powder is preferably first stirred before spraying in step 2), and second stirred during spraying, the first stirring rate is preferably 100-1000r / min, more preferably 300-800r / min, more preferably 500-600r / min, the first stirring temperature is preferably 25-50°C, more preferably 30-45°C, more preferably 35-40°C, the first stirring time is preferably 10-40min, more preferably 20-30min, more preferably 25min;

[0046] The spraying rate is preferably 1-40 mL / min, more preferably 10-35 mL / min, more preferably 20-30 mL / min, and the spraying temperature is preferably 40-80°C, more preferably 50-70°C, more preferably 60°C; the continuous mixing time is preferably 10-60 min, more preferably 20-50 min, more preferably 30-40 min; the stirring rates in the second stirring and the continuous mixing are independently preferably 100-1000 r / min, more preferably 300-800 r / min, more preferably 500-600 r / min.

[0047] In the present invention, the hydromagnesite powder is natural hydromagnesite powder.

[0048] In the present invention, the molar mass ratio of sugars and hydromagnesite powder in the sugar-containing mixed solution in step 2) is preferably 1-5 mol:10kg, more preferably 2-4 mol:10kg, and more preferably 3 mol:10kg; the median particle size of the hydromagnesite powder is preferably 1.0-4.5 μm, more preferably 1.5-4.0 μm, and more preferably 2.0-3.0 μm.

[0049] In the present invention, when the molar mass ratio of natural sugar to natural hydromagnesite powder is lower than 1 mol:10 kg, the amount of natural sugar added is too low, and it is difficult to effectively coat and modify natural hydromagnesite NMP, and it is difficult for the zirconium substrate layer to form an effective protective layer on the surface of natural hydromagnesite; however, when the molar mass ratio of natural sugar to natural hydromagnesite powder is higher than 5 mol:10 kg, the zirconium substrate layer will be too enriched on the surface of natural hydromagnesite NMP, and there will be multiple layers stacked on each other. During the preparation process, the natural hydromagnesite NMP powder particles may be wrapped together, resulting in a passive increase in the particle size of the coated natural hydromagnesite particles. During the processing, it is also easy to cause peeling and surface rupture under mechanical extrusion, thereby affecting the dispersion effect of the composite powder in the polymer.

[0050] In the present invention, the mass ratio of the zirconium-based mixed solution and the modified hydromagnesite composite powder in step 3) is preferably 1:0.05-0.8, more preferably 1:0.1-0.7, and more preferably 1:0.2-0.5; the mass molar ratio of the zirconium-based mixed solution and the silane coupling agent is preferably 1kg:0.1-2mol, more preferably 1kg:0.5-1.5mol, and more preferably 1kg:1.0-1.2mol;

[0051] The concentration of the silane coupling agent solution is preferably 1-10 mol / L, more preferably 3-8 mol / L, more preferably 5-6 mol / L. The solvent of the silane coupling agent solution is preferably an ethanol aqueous solution, and the volume ratio of ethanol to water is preferably 1:1-5, more preferably 1:2-4, and more preferably 1:3.

[0052] In the present invention, the silane coupling agent is an organosilane containing multiple functional groups.

[0053] In the present invention, the modified hydromagnesite composite powder is preferably first stirred before spraying in step 3), the first stirring rate is preferably 300-900r / min, more preferably 400-800r / min, more preferably 500-600r / min, and the first stirring time is preferably 10-60min, more preferably 20-50min, more preferably 30-40min.

[0054] In the present invention, the spraying rate of the zirconium-based mixed solution in step 3) is preferably 1-50 mL / min, more preferably 10-40 mL / min, and more preferably 20-30 mL / min; the spraying rate of the silane coupling agent solution is preferably 1-20 mL / min, more preferably 5-15 mL / min, and more preferably 10-12 mL / min. The temperature of the silane coupling agent solution is increased during the spraying process, and the temperature increase rate is preferably 5-20°C / min, more preferably 8-16°C / min, and more preferably 12-15°C / min. The target temperature is preferably 90-120°C, more preferably 100-110°C, and more preferably 105°C.

[0055] The continuous reaction time is preferably 10 to 30 min, more preferably 15 to 25 min, and more preferably 20 min; the stirring rate during the continuous reaction is preferably 500 to 1200 r / min, more preferably 700 to 1000 r / min, and more preferably 800 to 900 r / min.

[0056] In the present invention, the reaction product after the continuous reaction is completed is sequentially cooled, allowed to settle, dusted, and dried to obtain a zirconium substrate layered hydromagnesite composite powder; the cooling temperature is preferably 1 to 10°C, more preferably 3 to 8°C, and more preferably 5 to 6°C; stirring is performed during the cooling process, and the stirring rate is preferably 500 to 1200 r / min, more preferably 600 to 1000 r / min, and more preferably 800 to 900 r / min. The stirring time is preferably 10 to 30 min, more preferably 15 to 25 min, and more preferably 20 min; the settling time is preferably 10 to 60 min, more preferably 20 to 50 min, and more preferably 30 to 40 min; dust removal The power is preferably 100-600W, more preferably 200-500W, and more preferably 300-400W; the dust removal speed is preferably 300-1200r / min, more preferably 500-1000r / min, and more preferably 700-800r / min; the air inlet rate is preferably 5-15m / s, more preferably 7-13m / s, and more preferably 9-10m / s; the drying temperature is preferably 100-150°C, more preferably 110-140°C, and more preferably 120-130°C; the drying time is preferably 0.1-0.8h, more preferably 0.2-0.6h, and more preferably 0.4-0.5h; the air inlet volume is preferably 500-1250m 3 / h, more preferably 700 to 1050 m 3 / h, more preferably 750 to 950 m 3 / h.

[0057] The invention also provides a zirconium-based layered hydromagnesite composite powder prepared by the preparation method. The median particle size of the zirconium-based layered hydromagnesite composite powder is 1.0-5.0 μm.

[0058] In the present invention, the median particle size of the zirconium-based layered hydromagnesite composite powder is preferably 2.0 to 4.0 μm, more preferably 3.0 μm.

[0059] In the present invention, the zirconium-based layered hydromagnesite composite powder is white powder.

[0060] The zirconium substrate layered hydromagnesite composite powder (ZrO 2 -LFS-NMP) is shown in the following figure Figure 1 As shown by Figure 1 It can be seen that the functional layer between the natural hydromagnesite NMP and the zirconium substrate layer is the natural sugar silane bonding layer.

[0061] The invention also provides application of the zirconium-based layered hydromagnesite composite powder in a polyvinyl alcohol / gelatin composite material.

[0062] The zirconium substrate layered hydromagnesite composite powder of the present invention can be used as a functional composite filler in PVA functional films, and not only has good mechanical reinforcement properties, self-extinguishing properties, oxygen barrier properties, heat resistance enhancement properties, etc., but also can provide a good carbonization effect and achieve good green sustainability.

[0063] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0064] Example 1

[0065] The median particle size (D 50 ) is heat treated at 350°C in a nitrogen atmosphere for 30 min to obtain a zirconium substrate layer powder. The zirconium substrate layer powder is dispersed in an ethanol aqueous solution (the volume ratio of anhydrous ethanol to water is 1:10) at a dispersion rate of 3000 r / min for 60 min to obtain a zirconium-based mixed solution with a concentration of 5 mol / L.

[0066] 180.2 g of D-galactose was mixed with 425.7 g of bis(3-triethoxysilylpropyl)amine and dispersed in an ethanol aqueous solution (the volume ratio of anhydrous ethanol to water was 5:1) to obtain a sugar-containing mixed solution with a total concentration of sugar and silane of 2 mol / L.

[0067] 10 kg of natural hydromagnesite powder was placed in a high-speed mixer and stirred at a high speed of 500 r / min for 20 min at 40°C. Then, the sugar-containing mixed solution was added to the natural hydromagnesite powder by spraying. The spraying rate was 20 mL / min and the temperature was 60°C. After the spraying was completed, the stirring and mixing was continued at a rate of 500 r / min for 30 min to obtain a natural hydromagnesite composite powder modified with natural sugar and silane.

[0068] 0.2 kg of modified natural hydromagnesite composite powder was placed in a high-speed mixer and stirred at a high speed of 600 r / min for 30 min. Then, 1 kg of zirconium-based mixed solution was added to the modified natural hydromagnesite composite powder in the form of spraying (spraying rate was 30 mL / min). After the addition was completed, the temperature was raised to the target temperature of 100 ° C at a rate of 10 ° C / min. During the heating process, a silane solution containing 425.7 g of bis(3-triethoxysilylpropyl)amine was sprayed in the form of spraying (spraying rate was 10 mL / min). (the concentration of the solution is 5 mol / L, the solvent is ethanol aqueous solution, and the volume ratio of anhydrous ethanol to water is 1:2) is added to the mixed powder. After the addition is completed, the reaction is continued at a rate of 800 r / min for 15 minutes. The product after the reaction is completed is cooled to 5°C and stirred at a rate of 800 r / min for 15 minutes. After that, it is allowed to settle for 30 minutes and placed in a cyclone separator for dust removal. The dust removal power is 300 W, the rotation speed is 800 r / min, the air inlet speed is 10 m / s, and finally at 120°C at 750 m 3 / h air volume for flash drying, the flash drying time is 0.4h, and the zirconium substrate layer hydromagnesite composite powder (ZrO 2 -LFS-NMP).

[0069] The zirconium substrate layered hydromagnesite composite powder (ZrO 2 -LFS-NMP) particle size distribution diagram is as follows Figure 2 As shown. Figure 2 It can be seen that the particle size distribution of the zirconium substrate layer hydromagnesite composite powder prepared in this embodiment is relatively uniform, presenting a single peak, and concentrated in 2.0-4.0 μm.

[0070] The zirconium substrate layered hydromagnesite composite powder (ZrO 2 -LFS-NMP) Figure 3 As shown. Figure 3 It can be seen that there are more particle coatings on the surface of the composite powder, which are more evenly dispersed on the surface of natural hydromagnesite and are denser overall, indicating that the modification effect is better.

[0071] Example 2

[0072] The median particle size (D 50 ) is heat treated at 200°C in a nitrogen atmosphere for 60 min to obtain a zirconium substrate layer powder. The zirconium substrate layer powder is dispersed in a methanol aqueous solution (the volume ratio of methanol to water is 1:1) at a dispersion rate of 1200 r / min for 120 min to obtain a zirconium-based mixed solution with a concentration of 1 mol / L.

[0073] 378.3 g of D-trehalose was mixed with 34.2 g of bis(3-trimethoxysilylpropyl)amine and dispersed in a methanol-water solution (the volume ratio of methanol to water was 1:1) to obtain a sugar-containing mixed solution with a total concentration of sugar and silane of 1 mol / L.

[0074] 10 kg of natural hydromagnesite powder was placed in a high-speed mixer and stirred at a high speed of 100 r / min for 40 min at 25 °C. Then, the sugar-containing mixed solution was added to the natural hydromagnesite powder by spraying. The spraying rate was 1 mL / min and the temperature was 40 °C. After the spraying was completed, the stirring and mixing was continued at a rate of 100 r / min for 60 min to obtain a natural hydromagnesite composite powder modified with natural sugar and silane.

[0075] 0.05 kg of modified natural hydromagnesite composite powder was placed in a high-speed stirrer and stirred at a high speed of 300 r / min for 60 min. Then, 1 kg of zirconium-based mixed solution was added to the modified natural hydromagnesite composite powder by spraying (spraying rate was 1 mL / min). After the addition was completed, the temperature was raised to a target temperature of 90°C at a rate of 5°C / min. During the heating process, a silane solution (solvent) containing 34.2 g of bis(3-trimethoxysilylpropyl)amine was sprayed (spraying rate was 1 mL / min). The concentration of the liquid is 1 mol / L, the solvent is ethanol aqueous solution, and the volume ratio of anhydrous ethanol to water is 1:1) is added to the mixed powder. After the addition is completed, the reaction is continued at a rate of 500r / min for 30min. The product after the reaction is completed is cooled to 1°C and stirred at a rate of 500r / min for 30min. After that, it is allowed to settle for 10min and placed in a cyclone separator for dust removal. The dust removal power is 100W, the rotation speed is 1200r / min, the air inlet speed is 5m / s, and finally at 100°C at 500m 3 / h air volume for flash drying, the flash drying time is 0.8h, and the zirconium substrate layer hydromagnesite composite powder (ZrO 2 -LFS-NMP).

[0076] Example 3

[0077] The median particle size (D 50 ) is heat treated at 500°C in a nitrogen atmosphere for 1 min to obtain a zirconium substrate layer powder. The zirconium substrate layer powder is dispersed in a propanol aqueous solution (the volume ratio of propanol to water is 1:30) at a dispersion rate of 5000 r / min for 10 min to obtain a zirconium-based mixed solution with a concentration of 10 mol / L.

[0078] 180.16 g of D-mannose was mixed with 540.8 g of 1,2-bis(trimethoxysilyl)ethane and dispersed in an ethanol aqueous solution (the volume ratio of anhydrous ethanol to water was 10:1) to obtain a sugar-containing mixed solution with a total concentration of sugar and silane of 5 mol / L.

[0079] 10 kg of natural hydromagnesite powder was placed in a high-speed mixer and stirred at a high speed of 1000 r / min for 10 minutes at 50°C. Then, the sugar-containing mixed solution was added to the natural hydromagnesite powder by spraying. The spraying rate was 40 mL / min and the temperature was 80°C. After the spraying was completed, the stirring and mixing was continued at a rate of 1000 r / min for 10 minutes to obtain a natural hydromagnesite composite powder modified with natural sugar and silane.

[0080] 0.8 kg of modified natural hydromagnesite composite powder was placed in a high-speed mixer and stirred at a high speed of 900 r / min for 10 min. Then, 1 kg of zirconium-based mixed solution was added to the modified natural hydromagnesite composite powder by spraying (spraying rate was 50 mL / min). After the addition was completed, the temperature was raised to the target temperature of 120 ° C at a rate of 20 ° C / min. During the heating process, 540.8 g of zirconium-based mixed solution was sprayed (spraying rate was 20 mL / min). A silane solution of 1,2-bis(trimethoxysilyl)ethane (the concentration of the solution is 10 mol / L, the solvent is ethanol aqueous solution, and the volume ratio of anhydrous ethanol to water is 1:5) is added to the mixed powder. After the addition is completed, the mixture is stirred at a rate of 1200 r / min for 10 min to react. After the reaction is completed, the product is cooled to 10°C, stirred at a rate of 1200 r / min for 10 min, and then allowed to settle for 60 min. It is then placed in a cyclone separator for dust removal. The dust removal power is 600 W, the rotation speed is 300 r / min, the air inlet speed is 15 m / s, and finally at 150°C at 1250 m 3 / h air volume for flash drying, the flash drying time is 0.1h, and the zirconium substrate layer hydromagnesite composite powder (ZrO 2 -LFS-NMP).

[0081] Comparative Example 1

[0082] The 180.2 g of D-galactose in Example 1 was replaced by 90.1 g of D-galactose, and the other conditions were the same as in Example 1.

[0083] Comparative Example 2

[0084] The 180.2 g of D-galactose in Example 1 was replaced with 1081.2 g of D-galactose, and the other conditions were the same as in Example 1.

[0085] Comparative Example 3

[0086] The natural hydromagnesite powder (median particle size of 1.0 to 4.5 μm) obtained by multiple physical crushing, classification and screening was directly used without modification.

[0087] The zirconium substrate layered hydromagnesite composite powder (ZrO 2 -LFS-NMP) and the zirconium-based layered hydromagnesite composite powder (ZrO 2 -LFS-NMP) and unmodified high-mesh hydromagnesite powder were tested for activation rate and oil absorption value, and the test results are shown in Table 1.

[0088] Among them, activation rate: the dry powder is tested by weighing method; whiteness: the whiteness of various powders is tested using whiteness meter ADCI-2000; oil absorption value: tested according to DB / T5211.15-2014 standard.

[0089] Table 1 Test results of activation rate, whiteness and oil absorption value of the powders of the embodiments and comparative examples

[0090] Different powders Activation rate / % Whiteness / ° Oil absorption value (mL / 100g) Example 1 90.8 90.1 25 Example 2 85.5 85.3 27 Example 3 88.2 88.6 26 Comparative Example 1 38.5 78.3 34 Comparative Example 2 62.6 82.1 30 Comparative Example 3 14.3 92.0 39

[0091] As can be seen from Table 1, compared with Examples 1 to 3 and Comparative Example 3, the activation rate of the hydromagnesite composite powder after hybridization with the surface zirconium substrate layer shows a typical upward phenomenon, and the oil absorption value shows a significant downward trend, indicating that after modification with the zirconium substrate layer, the surface hydroxyl groups of the composite powder are greatly shielded, the surface polarity decreases significantly, and the subsequent adsorption degree of the processing aid is effectively reduced; It can be seen from Comparative Examples 1 to 3 that when the molar mass ratio of natural sugar to natural hydromagnesite is lower than 1 mol: 10 kg or higher than 5 mol: 10 kg, that is, when the content of the surface zirconium substrate layer is too low, the surface polarity of the composite powder does not decrease significantly, resulting in a limited number of zirconium substrate layers covering the surface, which is difficult to effectively cover the surface of natural hydromagnesite, and the surface modification effect is poor; when the content of the surface zirconium substrate layer is too high, too many surface zirconium substrate layers will cause multiple natural hydromagnesite powders to be wrapped together, the particle size becomes larger, and there is a strong physical adsorption effect on the surface, resulting in loose stacking on the surface, which may be peeled off during the processing, and the final activation rate is not significantly improved, and the oil absorption value is also limited. In addition, due to the introduction of the zirconium substrate layer with higher hardness, the whiteness of the composite powder is effectively protected. Among them, the whiteness value of the unmodified ultrafine natural hydromagnesite is 92.0. After being modified with a suitable proportion of zirconium substrate layers, its whiteness value has not decreased significantly. In contrast, when the proportion of zirconium substrate layers introduced on the surface is not appropriate, the whiteness value of the composite powder decreases significantly, indicating that a suitable proportion of zirconium substrate layers can effectively improve the whiteness of the natural hydromagnesite composite powder, making it less likely to be affected by other processing procedures. In summary, the surface polarity of natural hydromagnesite can be effectively improved through the zirconium-based layer to achieve a better shielding effect.

[0092] The zirconium substrate layered hydromagnesite composite powder prepared in Examples 1 to 3 and Comparative Examples 1 to 3 and the unmodified high-mesh hydromagnesite powder (median particle size of 1.0 to 4.5 μm) were added to the PVA / gelatin composite substrate. The specific process is: PVA and gelatin were dissolved in purified water (the concentrations of PVA and gelatin in the solution were both 15 wt%), the two solutions were mixed to obtain a mixed solution, the mass ratio of PVA to gelatin in the mixed solution was 7:3, and the mixture was stirred and heated to 90°C. After that, the various powders of the examples and comparative examples were added to the above-mentioned composite solution, mixed thoroughly and allowed to stand for degassing, and then the mixed solution was poured onto a plexiglass plate for tape casting, cooled and dried, and cast into corresponding standard samples and dried for subsequent testing.

[0093] Among them, mechanical properties test: control the tensile rate to 20mm / min; residual carbon rate test: in a nitrogen atmosphere, measure at a heating rate of 10℃ / min, and measure the ratio of the residual carbon mass to the initial mass at 600℃; flame retardant performance test: in accordance with GB / T 2406-2009 standard, prepare a test specimen of 150mm×20mm, and conduct a limiting oxygen index test on the sample; thermogravimetric test: take 5mg of sample, and in a nitrogen atmosphere, heat from 30℃ to 800℃ at a rate of 10℃ / min.

[0094] The performance test results of the composite powders prepared in Examples 1 to 3 and Comparative Examples 1 to 2 and the composite material prepared from the unmodified natural hydromagnesite in Comparative Example 3 are shown in Table 2.

[0095] Table 2 Performance test results of composite materials prepared in Examples and Comparative Examples

[0096]

[0097] It can be seen from Table 2 that when the zirconium substrate is layered with hydromagnesite composite powder (ZrO 2 -LFS-NMP) was added to the PVA / gelatin composite matrix (Examples 1 to 3), the tensile strength of the PVA / gelatin composite matrix showed a significant increase effect, from 35.5MPa to a maximum of 47.8MPa. When the molar mass ratio of natural sugar and natural hydromagnesite was too high or too low, the effect of the composite powder on improving the tensile strength of the PVA / gelatin composite matrix was significantly reduced (Comparative Examples 1 to 2).

[0098] In terms of the carbon residue rate at 600°C, the carbon residue rate of Examples 1 to 3 also shows a significant increase, indicating that the external zirconium substrate layer, the internal natural hydromagnesite and the natural sugars in the middle can effectively promote the increase in the quality of the carbon layer and have a good synergistic carbonization effect, increasing from 13.3wt% to a maximum of 22.3wt%. In comparison, the improvement effect of Comparative Examples 1 to 2 is limited, indicating that the synergistic effect of the outer shell and the inner core is very limited.

[0099] In terms of limiting oxygen index, ZrO 2 -The introduction of LFS-NMP can significantly improve the flame retardant effect of the PVA / gelatin substrate, increasing its oxygen index from 20.5% to a maximum of 27.8%, and its flammability is greatly improved. This is attributed to the fact that the zirconium substrate layer on the surface, the natural sugars in the middle, and the natural hydromagnesite inside all have good flame retardant effects. Combining the three together can achieve effective reconstruction of the multi-component multi-level structure and the synergistic effect of multiple functions; in contrast, the improvement of Comparative Examples 1 to 2 is limited, which is caused by the inappropriate proportions between the multiple components.

[0100] In terms of thermal properties, as ZrO 2-LFS-NMP was introduced into the PVA / gelatin composite substrate, and its maximum degradation temperature was increased from 310.5℃ to 325.3℃. This is because ZrO 2 -LFS-NMP contains heat-resistant components and MgO ceramic precursors produced during pyrolysis, which adhere to the pyrolysis surface and improve the pyrolysis performance. In contrast, ZrO 2 -LFS-NMP has limited effect on improving the thermal stability of PVA / gelatin substrate. 2 -LFS-NMP, the mechanical strength, carbon residue rate, limiting oxygen index and thermal stability of the PVA / gelatin substrate were improved significantly, which was closely related to the introduction of the layered structure of the zirconium substrate on its surface and the multi-level and multi-component structure.

[0101] The zirconium-based layered hydromagnesite composite powder of the present invention is first subjected to high temperature to promote local destruction of the zirconium phosphate sheet layer to form a zirconium-based layer with sheet defects and containing some zirconium oxide particles, and then natural sugar and traditional silane are mixed together and combined with natural hydromagnesite to obtain a hydromagnesite-based composite powder of natural sugar and traditional silane coupling hybrid; finally, the zirconium-based layer is added to the hydromagnesite-based composite powder. The zirconium-based layered hydromagnesite composite powder of the present invention not only has high hardness, low oil absorption value, good environmental protection, but also has good carbonization and smoke suppression properties, and can also be used as a multi-component organic-inorganic co-hybrid composite powder for composite material fillers, functional enhancers and processing promoters.

[0102] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a zirconium-based layered hydromagnesite composite powder, characterized in that: The following steps are included: 1) heat-treating zirconium phosphate powder to obtain zirconium substrate layer powder, and dispersing the zirconium substrate layer powder in a first solvent to obtain a zirconium-based mixed solution; mixing sugar, silane coupling agent and second solvent to obtain sugar-containing mixed solution; 2) spraying the sugar-containing mixed solution into the hydromagnesite powder, and continuously mixing after the spraying is completed to obtain a modified hydromagnesite composite powder; 3) Spraying the zirconium-based mixed solution and the silane coupling agent solution into the modified hydromagnesite composite powder in sequence, and continuing the reaction after the spraying is completed to obtain the zirconium-based layered hydromagnesite composite powder.

2. The preparation method according to claim 1, characterized in that: Step 1) The median particle size of the zirconium phosphate powder is 1.0-3.0 μm, the heat treatment is carried out in a nitrogen atmosphere, the heat treatment temperature is 200-500° C., and the heat treatment time is 1-60 min; the dispersion rate is 1200-5000 r / min, and the dispersion time is 10-120 min.

3. The preparation method according to claim 1 or 2, characterized in that: Step 1) The first solvent is an alcohol aqueous solution, in which the volume ratio of alcohol to water is 1:1 to 30; the alcohol includes ethanol, methanol, ethylene glycol, neopentyl alcohol, isopropanol or propanol; the second solvent is an ethanol aqueous solution, in which the volume ratio of ethanol to water is 1 to 10:

1.

4. The preparation method according to claim 3, characterized in that: Step 1) The concentration of the zirconium-based mixed solution is 1 to 10 mol / L; the molar ratio of the sugar to the silane coupling agent is 1:0.1 to 2.0, and the concentration of the sugar-containing mixed solution is 1 to 5 mol / L; The sugar comprises one or more of D-galactose, glucose, sialic acid, D-trehalose, sodium hyaluronate, sorbitol, glucosamine, D-mannose, sucrose, arabinose, N-acetyl-D-glucosamine, fructose, lactose, maltose, melibiose, xylose, lactulose, raffinose, erythritol, L-rhamnose, stachyose, D-tagatose, voglibose, lactobionic acid, D-allose, nesitose, alginic acid, maltitol, mannotriose, D-arabitol, sweet alcohol, D-lyxose and α-lactose; The silane coupling agent and the silane coupling agent in step 3) include one or more of bis-(3-(triethoxysilane)propyl)-disulfide, bis-(3-(triethoxysilane)propyl)-tetrasulfide, bis(3-triethoxysilylpropyl)amine, bis(3-trimethoxysilylpropyl)amine, 1,3,5-tris(trimethoxysilylpropyl)isocyanurate, 1,2-bis(triethoxysilyl)ethane and 1,2-bis(trimethoxysilyl)ethane.

5. The preparation method according to claim 4, characterized in that: Step 2) The hydromagnesite powder is first stirred before spraying, and a second stirring is performed during the spraying process, the first stirring rate is 100-1000 r / min, the temperature is 25-50° C., and the time is 10-40 min; The spraying rate is 1-40 mL / min, the temperature is 40-80° C., and the continuous mixing time is 10-60 min; the stirring rates in the second stirring and the continuous mixing are independently 100-1000 r / min.

6. The preparation method according to claim 4 or 5, characterized in that: Step 2) The molar mass ratio of sugars to hydromagnesite powder in the sugar-containing mixed solution is 1-5 mol:10 kg; the median particle size of the hydromagnesite powder is 1.0-4.5 μm.

7. The preparation method according to claim 6, characterized in that: Step 3) The mass ratio of the zirconium-based mixed solution to the modified hydromagnesite composite powder is 1:0.05-0.8; the mass molar ratio of the zirconium-based mixed solution to the silane coupling agent is 1kg:0.1-2mol; The concentration of the silane coupling agent solution is 1-10 mol / L, the solvent of the silane coupling agent solution is ethanol aqueous solution, and the volume ratio of ethanol to water is 1:1-5.

8. The preparation method according to claim 1 or 7, characterized in that: Step 3) before spraying, the modified hydromagnesite composite powder is first stirred at a rate of 300 to 900 r / min for 10 to 60 min; The spraying rate of the zirconium-based mixed solution is 1 to 50 mL / min, the spraying rate of the silane coupling agent solution is 1 to 20 mL / min, and the temperature of the silane coupling agent solution is increased during the spraying process, the temperature increase rate is 5 to 20° C. / min, and the target temperature is 90 to 120° C.; The continuous reaction time is 10 to 30 minutes, and the stirring rate during the continuous reaction is 500 to 1200 r / min.

9. The zirconium-based layered hydromagnesite composite powder prepared by the preparation method according to any one of claims 1 to 8, characterized in that: The median particle size of the zirconium-based layered hydromagnesite composite powder is 1.0-5.0 μm.

10. Use of the zirconium-based layered hydromagnesite composite powder according to claim 9 in a polyvinyl alcohol / gelatin composite material.